Shifting ranges of two tree weta species ( H emideina spp.): competitive exclusion and changing climate - Mariana Bulgarella; Steven A. Trewick; Niki A. Minards; Melissa J. Jacobson; Mary Morgan‐Richards (Journal of Biogeography, 2014)
Aim Species' responses to climate change are likely to depend on their ability to overcome abiotic constraints as well as on the suite of species with which they interact. Responses to past climate change leave genetic signatures of range expansions and shifts, allowing inferences to be made about species' distributions in the past, which can improve our ability to predict the future. We tested a hypothesis of ongoing range shifting associated with climate change and involving interactions of two species inferred to exclude each other via competition. Location N ew Z ealand. Methods The distributions of two tree weta species ( H emideina crassidens and H . thoracica ) were mapped using locality records. We inferred the likely modern distribution of each species in the absence of congeneric competitors with the software Maxent . Range interaction between the two species on an elevational gradient was quantified by transect sampling. Patterns of genetic diversity were investigated using mitochondrial DNA , and hypotheses of range shifts were tested with population genetic metrics. Results The realized ranges of H . thoracica and H . crassidens were narrower than their potential ranges, probably due to competitive interactions. Upper and lower elevational limits on M ount T aranaki over 15 years revealed expansion up the mountain for H . thoracica and a matching contraction of the low elevation limits of the range of H . crassidens . The observed nucleotide diversity in H . thoracica was consistent with a species that persisted in northern areas during Pleistocene glacial periods, from where it expanded at warmer times. In contrast, a two‐tailed distribution of nucleotide diversity in H . crassidens was as expected for a species that expanded northwards during glacials and southwards during interglacials. Main conclusions Range shifts resulting from climate change involve complex species interactions. Competition among related species is an important factor limiting realized ranges. In N ew Z ealand, H . thoracica is likely to continue to displace H . crassidens as human‐induced global warming proceeds.